Efektivitas Krim Ekstrak Daun Erythrina subumbrans (Hassk.) Merr. terhadap Diameter Luka Bakar Derajat IIA - Wardani, I Gusti Agung Ayu Kusuma; Udayani, Ni Nyoman Wahyu; Suena, Ni Made Dharma Shantini (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Burn injuries involve tissue damage caused by heat, including exposure to hot steam, fire, radiation, electricity, hot liquids or fats, electrical currents, and chemical compounds. Dadap Serep leaves (Erythrina subumbrans (Hassk) Merr) are among the plants recorded in Usada Bali, known for treating various types of wounds. This research aimed to assess the effectiveness of ethanol extract cream from Dadap Serep leaves in reducing the diameter of second-degree burns in vivo using white rats as test subjects. Twenty-four rats were randomly divided into four treatment groups: K- (negative control), K+ (positive control), P1 (application of Dadap Serep leaf extract cream 20%), and P2 (application of Dadap Serep leaf extract cream 40%). The cream was topically applied twice daily for 14 days. The burn diameter results were analyzed using SPSS 25 software employing the Tukey Test. Post hoc Tukey testing revealed significant differences between the negative control and positive control groups, treatments 1 and 2, with p-values of 0.001, 0.043, and 0.012, respectively. No significant difference was observed between the positive control group and treatment groups 1 and 2, with p-values of 0.268 and 0.596, respectively. The ethanol extract cream from Dadap Serep leaves proved effective in reducing the diameter of second-degree burns on rat skin. The Dadap Serep leaf extract cream at a concentration of 20% was effective in reducing the diameter of second-degree burns on rat skin.